The Influence of Education Through Media GEMILANG (Menstrual Hygiene Education Movement with Adventure) on The Knowledge of Female Adolescents - Tarissa Anandaputri; Nunung Mulyani; Laila Putri Suptiani (Jurnal Kebidanan, 2025)
Lack of understanding about hygiene during menstruation is still experienced by many adolescent girls, especially those who are about to or are experiencing menarche. The results of a preliminary study showed that 65% of female students do not know about menstrual hygiene. Innovation in learning methods is urgently needed, one of which is through the educational game media GEMILANG which was developed with an edutainment approach so that learning becomes more enjoyable and easier to accept. This study aims to determine the effect of education through GEMILANG media on increasing the knowledge of adolescent girls about menstrual hygiene. The study used a pre-experimental design with a one group pretest-posttest approach. The sampling technique used was a total sampling of 36 female students in grades 4–6 of SDN 2 Sukamanah who had not yet experienced menstruation. Data were analyzed using a Paired Sample T-Test. The results of this study showed an average pretest score of 38.47 which is included in the poor category then increased to 62.28 which is included in the sufficient category in the posttest, with an average difference of 23.81 and a significance value of p = 0.000 (p < 0.05), indicating a significant effect. Education through GEMILANG media is effective in increasing adolescent girls' knowledge about menstrual hygiene and can be an innovative learning medium in elementary school environments.